Picolinamide‐Based Iridium Catalysts for Aqueous Formic Acid Dehydrogenation: Increase in Electron Density of Amide N through Substituents. Issue 1 (24th November 2021) - Guo, Jian; Yin, Chengkai; Li, Maoliang; Zhong, Dulin; Zhang, Yuguan; Li, Xiaobin; Wang, Yilin; Yao, Hong; Qi, Tiangui
Abstract: Formic acid (FA) is considered to be a potential hydrogen storage material. Homogeneous catalysts are desired, which decompose aqueous FA into H2 and CO2 without addition of organic additives as they can contaminate the generated gas mixture. We report a new series of Cp * Ir (Cp * =pentamethylcyclopentadienyl) catalysts featuring picolinamide‐based ligands for efficient H2 generation from FA solution. Among them in‐situ generated catalyst from [Cp * Ir(H2 O)3 ]SO4 and picolinohydroxamic acid (L3 ) achieved a high turnover frequency (TOF) of 90625 h −1 at 80 °C in 0.9 M FA solution and a turnover number (TON) of 120520 at 80 °C in a recycle experiment. The substituent effect of amide N atom was discussed and a plausible mechanism was proposed based on the experimental results. Abstract : Formic acid (FA) is considered to be a potential hydrogen storage material. A new series of Cp * Ir (Cp * =pentamethylcyclopentadienyl) catalysts featuring picolinamide‐based ligands for efficient H2 generation from aqueous FA solution were presented. The substituent effect of amid N atom was discussed, and we considered the increase in electron density of amid N atom could enhance the reactivity. Newly synthesized in‐situ catalyst using [Cp * Ir(H2 O)3 ]SO4 and picolinohydroxamic acid achieved a high turnover frequency (TOF) of 90625 h −1 and a turnover number (TON) of 120520 at 80 °C. A plausible reaction mechanism was also proposed.